The role of international non-governmental organizations in non-international armed conflicts - Al-Badri, Raad Muhammad Hassan (Journal of Economic, Administrative and Legal Sciences, 2024)
International non-governmental organizations play an important role in the field of human rights, as they monitor human rights violations through the efforts made by these institutions to intervene with the relevant authority and before local and international public opinion, with the aim of putting an end to those violations. Accordingly, these organizations have the task of monitoring to protect the rights of society and its individuals from unjust behavior, and they work hard to defend the rights of every individual in society according to what is known of them. Considering that international non-governmental organizations protect human rights, which is increasingly important. Thousands of international and national organizations participate in an active role in promoting and protecting human rights, and also play a protection role when human rights instruments are not activated. Many of these organizations, with their various titles, have a consultative function in the Economic and Social Council of the United Nations, which helps them work within the framework of the Council and its subcommittees. It can also help in confronting human rights violations by submitting complaints and written reports to the Human Rights Council and expressing opinions during meetings held in various United Nations institutions. In addition, these organizations can conduct activities outside the United Nations to monitor human rights violations around the world, provide assistance to detainees, and file international complaints on their behalf.